2012
DOI: 10.1007/s00251-012-0601-9
|View full text |Cite
|
Sign up to set email alerts
|

The RIPK2 gene: a positional candidate for tick burden supported by genetic associations in cattle and immunological response of knockout mouse

Abstract: Ticks and tick-borne diseases have a detrimental impact on livestock production causing estimated losses of around $200 million per year in Australia alone. Host resistance to ticks is heritable, within-breed heritability estimates being around 0.35, and with large differences between breeds. Previously a QTL for tick burden was detected on BTA14 at ~72 Mb distal to the centromere, near the gene receptor-interacting serine-threonine kinase 2 (RIPK2). To identify polymorphisms in this region, we sequenced all e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…More than a hundred immune-related genes encoding cytokines, chemokines, CD markers, acute phase proteins, complement proteins, integrins, and TFs were found (Additional file 2: Table S2). Our results revealed novel DEGs associated with resistance/susceptibility, DEGs that support previous results and predictions, and DEGs that diverge with authors comparing gene expression between taurine and zebuine breeds [14, 2125], within other cattle breeds [2831] or murine models [37, 65]. According to Piper and colleagues [21, 23], CXCL2 and CCL2 were modulated only in S hosts; however, we found them also modulated in R. CCR1 and IL2R were described as modulated in R and CD14 in S [26], in contrast with our results where CCR1 and CD14 were modulated in both hosts, and IL2RG up-regulated only in S. IL8 was up-regulated in both R and S, but was previously described as down-regulated in R [33] and up-regulated in S [23].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…More than a hundred immune-related genes encoding cytokines, chemokines, CD markers, acute phase proteins, complement proteins, integrins, and TFs were found (Additional file 2: Table S2). Our results revealed novel DEGs associated with resistance/susceptibility, DEGs that support previous results and predictions, and DEGs that diverge with authors comparing gene expression between taurine and zebuine breeds [14, 2125], within other cattle breeds [2831] or murine models [37, 65]. According to Piper and colleagues [21, 23], CXCL2 and CCL2 were modulated only in S hosts; however, we found them also modulated in R. CCR1 and IL2R were described as modulated in R and CD14 in S [26], in contrast with our results where CCR1 and CD14 were modulated in both hosts, and IL2RG up-regulated only in S. IL8 was up-regulated in both R and S, but was previously described as down-regulated in R [33] and up-regulated in S [23].…”
Section: Discussionsupporting
confidence: 86%
“…3b). The importance of wound healing and structural proteins for tick resistance has been suggested [21, 37, 65]. Our results suggest the participation of WNT pathway in anti-tick resistance through an inflammatory scenario comprising the regulation of cytokines, receptors, matrix proteinases, and transcription factors and, at the same time, through its role in skin healing and remodeling, which hinders tick success.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The vitamin K epoxide reductase complex subunit like 1 ( VKORC1L1 ) was the most significant DEG in both comparisons (FDR < 5.4E-06). Interestingly, a relevant positional candidate gene for tick resistance RIPK2 [ 24 ] was found downregulated (logFC T12vsT0 = − 0.27, FDR T12vsT0 = 0.0026) in T12-vs-T0. Related to this, the interacting serine/threonine kinase 1 (RIPK1; logFC = − 0.3, FDR < 0.02) and gasdermin D (GSDM; logFC = − 0.4, FDR < 0.02) genes [ 39 ] were also found to be significant and downregulated in both timepoint comparisons, and gasdermin E (GSDE, logFC T3vsT0 = − 1.2, FDR T3vsT0 = 0.0024) downregulated only in T3-vs-T0 comparison.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, haplotypes that included the ITGA11 gene (integrin alpha 11) were significantly associated with tick burden and explained about 1.5% of the variation in the trait. Finally, the potential functional role of allelic variation in a gene identified by the same GWAS studies (Prayaga et al, 2009 ; Turner et al, 2010 ) RIPK2 (serine-threonine kinase 2) was further examined using knock out mice (Porto Neto et al, 2012 ). This gene is known to play an essential role in the modulation of innate and adaptive immune responses and it was found that it influenced the recognition of tick salivary antigens by mice.…”
Section: Molecular Genetic Variants Associated With Host Resistancementioning
confidence: 99%